The role of chemical and mineral supplements in the development of highly durable concrete structures (Texas Journal of Engineering and Technology, 2022)
Modern construction practice involves the widespread use of chemical additives in concrete. As a chemical additive, there is not a kind of effective, universal and easy-to-use tool for radically changing the properties of concrete mixture and concrete.